Editorial: tissue findings fail to predict disease activity or prognosis in microscopic colitis—an opportunity to look at the molecular level—authors' reply. Issue 2 (25th June 2021) - Olsen, Lærke Müller; Engel, Peter Johan Heiberg; Goudkade, Danny; Villanacci, Vincenzo; Thagaard, Jeppe; Walbech, Julie Sparholt; Bohr, Johan; Kupcinskas, Juozas; Verhaegh, Bas; Münch, Andreas; Guagnozzi, Danila; Fernández‐Bañares, Fernando; et al.
LINKED CONTENT: This article is linked to Olsen et al and Lucendo papers. To view these articles, visit https://doi.org/10.1111/apt.16381 and https://doi.org/10.1111/apt.16403